The consumption of fashion and the construction of identity of the adolesc - Tostes, Francyelle Ribeiro (2017)
The purpose of this article was to investigate the influence of fashion consumption on the identity construction, during adolescence. For this, a literature review, an analysis of advertising images and a qualitative survey was conducted . This way, we verified the positivity of fashion consumption in this process, as a tool to compose and express the personality of the adolescent. However it was found that the strategies used by the fashion marketing to young people, can be harmful and cause problems in the acceptance of self-image.Keywords: fashion consumption; identity construction; self-image; marketing.